The structural and optical constants of Ag2S semiconductor nanostructure in the far-infrared - Zamiri, Reza; Ahangar, Hossein Abastabar; Zakaria, Azmi; Zamiri, Golnoosh; Shabani, Mehdi; Singh, Budhendra; Ferreira, J.M.F. (Chemistry Central, 2015)
Background In this paper a template-free precipitation method was used as an easy and low cost way to synthesize Ag2S semiconductor nanoparticles. The Kramers–Kronig method (K–K) and classical dispersion theory was applied to calculate the optical constants of the prepared samples, such as the reflective index n(ω) and dielectric constant ε(ω) in Far-infrared regime.